Complementarities between policy actions in software production in emerging economies. The case of Argentina - Motta, Jorge (2013)
Fil: Motta, Jorge. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.